Eat Chew Live : 4 Revolutionary Ideas to Prevent Diabetes, Lose Weight and Enjoy Food - Poothullil, John M. (Los Angeles, CA : Over and Above Press, Over and Above Creative Group, 2015)
"Dr. Poothullil's thoughtful recommendations about how to eat and enjoy food will gently guide you to lose pounds, empty your fat cells, and return to your 'authentic weight.' If you are on diabetes medications, you may be able to reduce or even stop them." --
Part 1. A revolutionary new theory about the cause of diabetes -- Part 2. How your body takes care of itself -- Part 3. Reconnecting with your authentic weight -- Part 4. Eat what you enjoy & enjoy what you eat.
Includes bibliographical references and index.
Keywords: Diabetes -- Diet therapy; Weight loss; Reducing diets; Non-insulin-dependent diabetes -- Popular works; Self-care, Health